The mediating effect of happiness on the relationship between work-life balance and life satisfaction: an empirical study on employees of Malaysian financial industry / Siti Hartini Najamudin, Muhamad Khalil Omar and Azzarina Zakaria - Najamudin, Siti Hartini; Omar, Muhamad Khalil; Zakaria, Azzarina (Penerbit UiTM (UiTM Press), 2017)
The issue of happiness in organisation has been debated among academicians, practitioners, and policy makers nowadays. This is because it provides an index of how well things are going within the organisational context. The ability for an organisation to track front-line employee’s happiness over time is a very useful in order to achieve organisation’s successful policies and practices. Some previous studies conducted to measure the relationship contribute of work-life balance effects in quality in life, life satisfaction and wellbeing. Also, the impact of decreased income on happiness has hardly been studied except through the drop in income due to unemployment. Therefore, this paper attempts to show the relationship of work-life balance and life satisfaction with the mediating role of happiness. The main problem is to relate the situation to the Malaysian Financial Sector work-life balance with sense of happiness by World Happiness Report to get the outcomes of life satisfaction. Perhaps for these reasons, towards the end of this paper, happiness is proposed to be measured in mediating concept by linking the relationship of work-life balance and life satisfaction.